KOMUNIKASI EMPATIK SATUAN TUGAS GEGER UNTUK MENDUKUNG PERAN CAREGIVER DALAM MENINGKATKAN PEMULIHAN PASIEN GANGGUAN JIWA - Sheila Heza Aurora; Sri Wahyuningsih (LPPM Stikosa - AWS, 2026)
Families are at the forefront as companions to patients with mental disorders in their daily lives, such as helping them comply with treatment and providing emotional support. As caregivers, families often receive little attention in terms of mental, psychological, and emotional support from relevant parties. One form of support to optimize the role of caregivers is through effective communication. The Geger Task Force Team uses an empathetic communication approach with caregivers so that they feel heard and supported, giving them the strength to perform their roles optimally, which will ultimately have an impact on the patient's recovery process. This study was conducted to explore in depth the forms and patterns of empathetic communication applied by the Geger Task Force in supporting the role of caregivers and to identify the factors that hinder the application of empathetic communication between the Geger Task Force and caregivers, which affect the recovery process of patients with mental disorders. A qualitative research method with a case study approach was used. Research data sources were obtained from interviews and direct observations, audio-visual recordings, photographs, and research-related archives. Empathetic communication was implemented more actively through home visits as the main means of providing emotional, informational, and instrumental support, as well as appreciation. However, the effectiveness of this communication and empowerment was hampered by three factors. Although the Geger Task Force played an active role, the success of patient recovery also depended on cooperation between institutional initiatives and the openness of the families of patients with mental disorders. Keywords: Caregiver, Communication, Empathetic , ODGJ, Recovery, Task Force